Pratiques et organisation spatiale de la plage de Dadonghai à Sanya (île de Hainan, Chine) - Benjamin Taunay; Luc Vacher (M@ppemonde)
Beaches in China are regularly presented as a space that symbolizes the access of new populations to the phenomena of tourism, within the framework of globalization. These spaces are the stage on which original practices are developing. They inform us on the evolution of societies in their access to the leisure activities. This article is based on the study of the beach of Dadonghai on the tropical island of Hainan in South China. It explores the specificities of the Chinese beach and presents the originality of practices, the rhythms of attendance and the spatial organization of the beach.